Serum CA19-9 Response to Neoadjuvant Therapy Predicts Tumor Size Reduction and Survival in Pancreatic Adenocarcinoma - Al Abbas, Amr I.; Zenati, Mazen; Reiser, Caroline J.; Hamad, Ahmad; Jung, Jae Pil; Zureikat, Amer H.; Zeh, Herbert J.; Hogg, Melissa E. (Annals of surgical oncology, 2020)
Background The optimal cutoffs for carbohydrate antigen 19-9 (CA19-9) response after neoadjuvant therapy (NT) for pancreatic adenocarcinoma (PDAC) are not well characterized. This study aimed to analyze the relationship of serum CA19-9 to other markers of response and to identify thresholds correlating to outcomes. Methods A retrospective review of resected PDAC patients from 2010 to 2017 at an academic tertiary referral center was conducted. Results The analysis enrolled 250 subjects. Normalization and multiple cutoff points for CA19-9 response were assessed. Normalization was not associated with improved survival (35.17 vs. 29.43 months; p = 0.173). Although a response 45% or higher was associated with longer survival (35 vs. 20 months; p = 0.018), a response of 85% or higher was optimal (55.7 vs. 25.97 months; p < 0.0001). A response of 85% or higher remained a strong independent predictor of survival [hazard ratio (HR), 0.47; p = 0.007]. Subjects with a response of 85% or higher had received more NT cycles [3 (range 2–6) vs. 3 (range 2–4) cycles; p = 0.006] and fewer adjuvant cycles [4 (range 3–6) vs. 5 (range 3–6) cycles; p = 0.027]. Reduction in T-size correlated with a drop in CA19-9 and a size reduction of 25% or higher (56.97 vs. 28.17 months; p = 0.016) improved survival. A serum CA19-9 response of 85% or higher was a strong independent predictor of a reduction in T-size of 25% or higher (HR 2.40; p = 0.007). Conclusion A CA19-9 response of 85% or higher is the optimal threshold for predicting survival. It is predictive of T-size reduction. Future NT trials should incorporate CA19-9 response as an end point.